Effects of Environmental Regulation Competition and Public Participation on Enterprise Location Selection Under Climate Change in COVID-19 Pandemic Conditions: An Analysis Based on the Chinese Provincial Spatial Panel Model - Mu, Xiuzhen; Zhan, Qilin; Ameer, Waqar; Anser, Muhammad Khalid; Zeng, Xiaohui; Amin, Azka (Frontiers in Environmental Science, 2022)
The deterioration of environmental quality has attracted the attention of the Chinese government and the public. The Chinese government has delegated part of the power of environmental regulation to local governments. To fulfill the KPI, local governments tend to loosen environmental regulations to attract more settlement of enterprises, thus; leading to an increasingly fierce local environmental regulation competition. The improvement of people's living standards makes it possible for the public to participate in environmental regulation. The article seeks to carry out the empirical study to interpret the relationship between local environmental regulation competition, public participation and enterprise location selection through a random-effects spatial Durbin model with 29 provincial panel data in China from 2004 to 2017. The results show that the provincial spatial spillover effect of enterprise location selection is significant. More intensified local environmental regulation competition can attract more investment but may harm sustainable economic development. Active public participation can effectively avoid the excessive investment caused by local environmental regulation competition and sustain economic development. Therefore, we should establish and improve the local environmental prevention and regulation system. Establishing an information disclosure mechanism to ensure public participation. The local government's environmental regulation and public participation mechanism should be effectively coordinated.